Teacher’s Strategy In Teaching Vocabulary To Deaf Or Hard-Of-Hearing Students - Yanti Suryanti; Deddy Sofyan; Mursidah Rahmah; Upi Dahlia (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
Deaf students are students who have little or no speech depending on the severity of the hearing loss, meanwhile hard of hearing students are students who may have speech impairments as a result of their inability to hear their own voices clearly. By applying the qualitative approach with the descriptive method, the study depicts the strategy used by the teacher in teaching vocabulary to seven students of the eleventh grade at SLB Dharma Wanita-Bogor, which was conducted from May 15 to December, 15th 2022. The data were collected through observation, documentation, and interview. The observations were done from August to September 2022, meanwhile, the interview was on 15th October 2022. The participants of the study were two targeted English teachers at SLB Dharma Wanita-Bogor who fulfilled the criteria that they have a background in teaching English, have been teaching English for more than 5 years, are qualified, and are experienced in teaching deaf students. From the observations, the documentation, and the interview, it is revealed that both teachers had carried out the steps written in their lesson plans completely, and the strategy used by both teachers are repetition, lip reading, gesture, body movement, through-the-air language comprehension, and the use of media. In lip reading and through the air communication, they pronounced each word carefully and slowly and asked each student to repeat what they said, used the media/pictures which are available in the class, and asked the students to look up the dictionary to find the words. If the students still find difficulties in saying the words, both of the teachers used sign language, through air conversation or body movement. They confess that the students so far can follow the lesson well, and their final grades are considered enough until good.